Voxelotor: novel drug for sickle cell disease - Singh, Jasjit; Maggo, Sachin; Sadananden, Uthara K. (International Journal of Basic & Clinical Pharmacology, 2020)
Sickle cell disease (SCD), is an autosomal recessive disorder caused by mutation in the β‐chain of haemoglobin (Hb) that leads to production of sickle haemoglobin (HbS). The disease has a profound negative impact on health-related quality of life with increased propensity for complications. Current treatment options include drugs like hydroxyurea and L-glutamine that are currently on the market. However, none of these therapies target the underlying mechanism and have potential safety concerns. As oxygenated Hb is a potent inhibitor of HbS polymerization, increasing the proportion of oxygenated HbS may provide a disease‐modifying approach to SCD. Voxelotor is a novel therapy developed for the treatment of SCD by modulating the Hb affinity for oxygen. By forming a reversible covalent bond with the N‐terminal valine of the α‐chain of Hb, the drug results in an allosteric modification of Hb and thereby leading to an increase in oxygen affinity. Moreover, voxelotor prevents sickling of red blood cells (RBCs) and possibly interrupts the molecular pathogenesis of the disease. The drug is available in oral formulation with a recommended dosage of 1500 mg once daily. The onset of voxelotor is fast, shows rapid absorption and linear pharmacokinetics. Most common adverse reactions seen are headache, diarrhea and abdominal pain. Clinical trials for voxelotor have been positive, and results suggest that the drug may be a new safe and effective option for SCD treatment. With global blood therapeutics having already received US FDA approval in November 2019, voxelotor may soon be an addition to the mounting armoury of drugs against SCD.